THE STATUS OF E-LEARNING IN THE 4.0 EDUCATION ERA (DESCRIPTIVE STUDY OF INFORMATIC ENGINEERING STUDENTS - Hermila A Hermila A; Rahmat Taufik R.L Bau Rahmat Taufik R.L Bau (Journal of Scientech Research and Development, 2022)
The development of technology and revolution 4.0 is challenging in the education sector. The era of education has adjusted to the 4.0 revolution era, where the integration of digital technology is the main thing in the implementation of education. One way to be done is to take advantage of digital technology through e-learning. This study aims to see the position of e-learning based on the perspective of students or students in the Informatics Engineering department. This study used a quantitative approach with a descriptive study model conducted at the Informatics Engineering Department, Faculty of Engineering, State University of Gorontalo. Respondents were 87 students majoring in Informatics Engineering. The research instrument used questionnaires and interviews. Data analysis using descriptive statistics. The indicators related to the position of e-learning assessed are (1) student perceptions regarding the use of e-learning in learning and (2) the position of e-learning in the education era 4.0 based on student perceptions. The study's results found: (1) Learning by utilizing e-learning to support learning can run both theoretical and practical material optimally according to student perceptions. (2) The position of e-learning is essential in the era of education 4.0. not only as a system but a multifunctional switch to become a container and learning media. (3) Most students choose the game-based e-learning model of their interest in the learning process using e-learning